2017
DOI: 10.1186/s13098-017-0287-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in United Arab Emirates Expatriates: the UAE National Diabetes and Lifestyle Study

Abstract: ObjectiveTo describe current prevalence of obesity and related non-communicable diseases (NCDs) in expatriates living in the United Arab Emirates (UAE).MethodsWe used data from the cross-sectional UAE National Diabetes and Lifestyle Study (UAEDIAB), which surveyed adult expatriates living in the UAE for at least 4 years. We report crude prevalence of overweight and obesity, indicated by gender and ethnicity-specific body mass index (BMI), waist circumference (WC) and waist-to-hip ratio (WHR) cut-offs, by lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 23 publications
4
83
1
1
Order By: Relevance
“…The present study findings revealed that obesity was significantly lower among males (9.4%) than females (19.3%), which was consistent with those of other studies on obesity (6,18,21,(24)(25)(26). In the gender ratio of the participants (i.e., M:F = 0.63), Vania et al, reported that the prevalence of obesity was 32% and 25% among females and (27).…”
Section: Discussionsupporting
confidence: 92%
“…The present study findings revealed that obesity was significantly lower among males (9.4%) than females (19.3%), which was consistent with those of other studies on obesity (6,18,21,(24)(25)(26). In the gender ratio of the participants (i.e., M:F = 0.63), Vania et al, reported that the prevalence of obesity was 32% and 25% among females and (27).…”
Section: Discussionsupporting
confidence: 92%
“…This is because 74% of participants were employed with a signi cant proportion earning above 500 Kuwaiti Dinah (Table S1) -many of whom are expatriates or locals in high income employments. Several possible drivers of this patterning between overweight and obesity is attributed to a strong culture of physical inactivity and smoking [45], and beliefs that view individuals with obese physique as appealing and sign of a uence [46]. Also, the unemployed were less likely to be overweight and obese compared to those employed, after accounting for other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study only focussed on Emirati nationals, who are the only ones obliged to undergo the compulsory medical examination, other studies conducted over the last decade have reported high prevalence rates of obesity and of diabetes in expatriates residing in the UAE, particularly in those who were ethnic Arabs or South Asians. 17,18 Our study only investigated men, but a recent (2013-2014) study of 555 young female university students in the UAE aged 17-25 years reported that 23.1% of these young women were overweight and 10.4% as obese, with 6.8% already fulfilling criteria for metabolic syndrome. 19 The prevalence of obesity is thus lower than in the young men of the same age range in our study.…”
Section: Discussionmentioning
confidence: 99%